(untitled) (Bangladesh Journal of Botany, 2022)
Morphological, phenological characterization and conservation management of Hedychium borneense R.M.Sm, a terrestrial-epiphytic herb and endemic to Kalimantan, Borneo are described. Results revealed that H. bornensee has a purple-brownish bractea, a terminal and raceme inflorescence, pale yellow flowers with a broad and pale-yellow labellum and orange stamen, a triocular fruit with an orange to red inner color, and brownish seeds with a dark red arillus. There are six phenology phases: initiation phase, flower development phase, pre-anthesis phase, anthesis phase, post-anthesis phase, and fruit development. Flower development lasts for 34 days, with a two-day anthesis phase in between. The ripe fruit occurs on day 94. It grows best in porous, moist environment; sphagnum moss and sand mix compost (1:1) is the best media for this plant. Since the plant is endemic, ex-situ conservation management through generative propagation is observed to be essential. Bangladesh J. Bot. 51(2): 313-323, 2022 (June)